Legalizing passive euthanasia: a comparative study between Malaysia and India / Farah Nazreen Mirza Mohammad Taiyab Beg, Irdina Azizi and Aramy Rasyid Mohamed - Mirza Mohammad Taiyab Beg, Farah Nazreen; Azizi, Irdina; Mohamed, Aramy Rasyid (2014)
This research compares the position of passive euthanasia in Malaysia and India. This research aims to legalize the act of passive euthanasia in Malaysia. In the comparative study, the purpose is focused on why passive euthanasia should be legalized in Malaysia whereby India has taken a positive stand. The research has been carried out to collect as many evidence and reason to support the legalization of passive euthanasia in Malaysia. The comparison is made with India because India and Malaysia are Commonwealth countries. Besides that, Malaysia's Penal Code is based on the Indian Penal Code. The act of euthanasia is a crime under Section 299 amd 300 of Malaysian Penal Code. India had taken the positive stand by legalizing passive euthanasia with certain requirement fulfilled. Therefore this research mainly compares Malaysia's Law with Indian Law.